Verbe remettre et ses équivalents polonais. Désambiguïsation et analyse sémantico-préfixale pour les besoins de la traduction automatique - Hrabia, Michał (Neophilologica, 2018)
The present paper aims at presenting the results of the disambiguation procedure of the French polysemic verb remettre. Each meaning of the analysed word is illustrated with examples, associated with the Polish translation and properly formalized with the use of syntactic-semantic schemes (being one of the formats of the computational lexicographic description proposed in the object-oriented approach by Wiesław Banyś). Furthermore, in the second part of the article, the author examines the prefixed equivalents of remettre and tries to establish some semantic relations between the French and Polish prefixation process.